2013
DOI: 10.1002/ppul.22882
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ethnicity and extreme prematurity on infant pulmonary function

Abstract: The impact of birth before 27 completed weeks of gestation on infant pulmonary function (PF) was explored in a multi-ethnic population in comparison to more mature preterm controls (PTC) and healthy fullterm infants. Plethysmographic lung volume (FRCpleth) and forced expired volume (FEV0.5) were obtained at ∼12 months post-term age in 52 extremely preterm (EP) infants (median [range] gestational age [GA]: 26 [23–27] weeks; 40% White mothers; 79% with BPD), 41 PTC (GA:35 [30–36] weeks; 37% White mothers) and 95… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
3
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 43 publications
2
36
3
4
Order By: Relevance
“…Our findings of boys with airway obstruction compared with girls are consistent with prior reports (27,(34)(35)(36), and the finding of black infants with increased airway obstruction compared with white infants also supports previous studies (37)(38)(39). The responsiveness to bronchodilators in our study (29% of infants) is comparable to that reported by Goldstein and colleagues (40), who found response to albuterol in 20 to 25% of a small cohort of healthy infants and young children born at more than 36 weeks of age, and to those of Debley and colleagues, who reported a bronchodilator response in 24% of 76 infants with recurrent wheezing (41).…”
Section: Original Researchsupporting
confidence: 83%
“…Our findings of boys with airway obstruction compared with girls are consistent with prior reports (27,(34)(35)(36), and the finding of black infants with increased airway obstruction compared with white infants also supports previous studies (37)(38)(39). The responsiveness to bronchodilators in our study (29% of infants) is comparable to that reported by Goldstein and colleagues (40), who found response to albuterol in 20 to 25% of a small cohort of healthy infants and young children born at more than 36 weeks of age, and to those of Debley and colleagues, who reported a bronchodilator response in 24% of 76 infants with recurrent wheezing (41).…”
Section: Original Researchsupporting
confidence: 83%
“…Following successive government strategies to tackle smoking in the UK,29 smoking prevalence in London mothers has fallen over the past decade from ∼40% in the 1990s15 30 to around 16% currently 8. The lack of association between tobacco smoke exposure and LF in infants studied using the Jaeger equipment, probably reflects the recent low exposure rates.…”
Section: Discussionmentioning
confidence: 99%
“…RVRTC data from healthy infants and children <2.5 years of age collected using the Jaeger BabyBody were available from four specialised paediatric centres in the UK, Spain, Portugal and Australia as described previously 5 8 12–14. Similar data collected using the RASP system were also available from the UK centre 3 15.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been extensively studied in animal experiments and has been explained by diminished angiogenesis that is the growth limiting factor of alveolarisation [21]. This results in an underdevelopment of the pulmonary vasculature and in fewer but larger alveoli, with fewer alveolar attachments, and increased airway resistance and work of breathing [22], and is associated with diminished level and abnormal development of lung function in former pre-terms with or without a history of artificial ventilation [23][24][25]. These studies of early lung function following prematurity do not demonstrate any catch-up of airway function in the first year and even a relative deterioration compared to normals.…”
Section: @Erspublicationsmentioning
confidence: 99%